Express in simplest form: 1 - 1/x / 1/x^2 - 1/x A) x B) -x C)1/x D) -1/x
- print Print
- list Cite
Expert Answers
jeew-m
| Certified Educator
calendarEducator since 2012
write1,657 answers
starTop subjects are Math, Science, and Social Sciences
`(1-1/x)/(1/x^2 - 1/x)`
`= ((x-1)/x)/((1-x)/x^2)` By getting the common denominator
`= (-(1-x)*x^2)/((1-x)x)`
`= -x^2/x`
`= -x`
So the correect answer is B).
check Approved by eNotes Editorial
Related Questions
- Using properties of determinant prove that `|[1, a, a^2],[1, b, b^2],[1, c, c^2]| = (a-b)(b-c)(c-a)`
- 1 Educator Answer
- The incentre of the triangle formed by the lines y=|x| and y=1 is A) (0, 2 - √2) B) (2 - √2 ,...
- 1 Educator Answer
- Which of the following is a factor of both x^2-x-6 and x^2-5x +6? A. x-3 B. x+3 C. x-2 D x+2
- 1 Educator Answer
- f(x)= x^2 - 4x + 5 , x > 2 a) Express f(x) in the form (x+b)^2 + c b) State the range of f...
- 1 Educator Answer
- if a^x=b^y=c^z and b^2=ac Prove that, 1/x+1/z=2/y.
- 1 Educator Answer